Role of laparoscopic cholecystectomy in atypical/asymptomatic gall stone disease patients: a randomized controlled trial from a tertiary care centre in North India - Mohan, Ajay; Kushwaha, Anurag; Srikanth, Muppana Veerabhadra Venkata Sai; Gupta, Mehul; Rathore, Yashwant Singh; Chumber, Sunil (International Surgery Journal, 2024)
Background: Gallstone disease (GSD) exhibits considerable heterogeneity, ranging from biliary colic to severe complications such as acute cholecystitis and gallstone pancreatitis. The majority of cases have no prior history of biliary symptoms and are diagnosed incidentally, often labelled as "asymptomatic GSD." Detailed questioning often reveals the presence of vague abdominal discomfort such as pain, dyspepsia, and flatulence. Methods: In this study, we randomized patients with asymptomatic or atypical gallstone disease into two groups: Group A (Control group) and Group B (Interventional group), where standard laparoscopic cholecystectomy was performed. All patients were followed up at 1 week, 6 months, and 12 months to monitor the development of biliary symptoms, postoperative complaints, and the impact on atypical gastrointestinal symptoms. Results: The results showed no significant change in atypical symptoms from the initial presentation at the 1-year follow-up in the control group. There were no serious biliary complications or hospitalizations for this subgroup of patients. Among the 13 patients in the observation arm, three (23.1%) underwent laparoscopic cholecystectomy due to the development of biliary colic during the follow-up. Conclusions: In conclusion, laparoscopic cholecystectomy does not appear to improve atypical abdominal symptoms or decrease the risk of gallbladder carcinoma in patients with asymptomatic GSD from North India. However, surgical intervention may be offered to patients with large stone sizes, as they are at increased risk of becoming symptomatic within 1 year, as observed in our study.